2022
DOI: 10.3389/fonc.2022.834068
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Psychosocial Distress and Unmet Needs in Older Patients With Head and Neck Cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the most common cancer involving the mucosal surfaces of the head and neck and is associated with a number of etiological factors, including cigarette smoking, alcohol and betel nut consumption and exposure to high-risk human papillomavirus. The risk of HNSCC increases with age, peaking in the seventh and eighth decade, but this varies by anatomical and histological subtype. While several advancements have been made in the treatment of head and neck cancer (HNC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 214 publications
(149 reference statements)
0
8
0
Order By: Relevance
“…For patients receiving CCR, we identified important psychosocial risk factors associated with RNC utilization, including unpartnered marital status and referral for psychosocial oncology assessment. Previous work has shown that caregivers play a crucial role in promoting self-care and supporting patient needs, not only for cancer patients but also for those with other chronic diseases; indeed, a lack of social support is a predictor of poor outcomes [ 24 , 25 , 26 , 27 , 28 ]. The concept of psychosocial vulnerability has not been previously identified as a risk factor for acute care utilization, specifically within oncology populations.…”
Section: Discussionmentioning
confidence: 99%
“…For patients receiving CCR, we identified important psychosocial risk factors associated with RNC utilization, including unpartnered marital status and referral for psychosocial oncology assessment. Previous work has shown that caregivers play a crucial role in promoting self-care and supporting patient needs, not only for cancer patients but also for those with other chronic diseases; indeed, a lack of social support is a predictor of poor outcomes [ 24 , 25 , 26 , 27 , 28 ]. The concept of psychosocial vulnerability has not been previously identified as a risk factor for acute care utilization, specifically within oncology populations.…”
Section: Discussionmentioning
confidence: 99%
“…When considering Qol 1 year after RT treatment, pain presence is still severe and can interfere in patients QoL. Additionally, other pain-related aspects in cancer patients have been proposed as relevant when exploring Qol like medication intake and psychoemotional distress [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a matter of debate in the older HNSCC population [ 6 – 8 ], concomitant chemotherapy is commonly applied simultaneously to definitive radiotherapy for locoregionally advanced HNSCCs. Radiotherapy can result in considerable both acute and chronic toxicities in HNSCC patients, severely impacting patients’ quality of life (QoL) [ 9 , 10 ], conformal treatment techniques such as intensity-modulated radiotherapy (IMRT) have been shown to reduce treatment-related toxicities, as relevant organs at risks (OARs) such as the parotid glands or the pharyngeal constrictor muscles (PCMs) can be spared [ 11 , 12 ]. Proton IMRT may further reduce the risk of treatment-induced normal tissue injuries in HNSCC patients and is currently investigated in clinical trials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%